Construire ou déconstruire l’espace du Raval dans En construcción (José Luis Guerin, 2001) ? - Marianne Bloch-Robin (Catalonia)
This article analyzes the construction of the cinematic space in José Luis Guerin’s documentary En Construccion (2003). The visual and sound elements are combined to shape the space of the neighborhood-city: that of the closed microcosm of the changing Barrio Chino, which traps its inhabitants destined for disappearance; that of the palimpsests of temporalities and finally the complementary spaces of the « here », « there » and « elsewhere », according to the terminology defined by André Gardies, these two last dimensions being particularly introduced through sound in the apparently closed Barcelona neighborhood of Raval.